Spiritual Therapy: Dzikir and Worship on Patient’s Ability to Control Violent Behavior in Mental Hospital - Retno, Retno Twistiandayani; Hadi Prayoga, Dimas; Nora Ervina, Icha (Jurnal Ilmiah Kesehatan, 2024)
Violent behavior is when someone engages in actions that can cause physical harm to themselves, others, or the environment. This research aims to analyze the effect of spiritual therapy prayer, dzikir, on patients' ability to control violent behavior. The research design employed a Pre-Experiment approach with a Pretest-Posttest Control Group Design. The target population included all Muslim patients with a history of violent behavior who were physically healthy and cooperative in the Gelatik Room at Menur Mental Hospital, Surabaya, totaling 27 people. A probability sampling technique, specifically simple random sampling, was used for the sampling method. The independent variable was spiritual therapy prayer and worship, while the dependent variable was the patient's ability to control violent behavior. The instrument used is the Standard Operational Procedure (SOP), and data were analyzed using the Wilcoxon Rank Test statistical test. The results of the Wilcoxon Rank Test in the treatment group (p = 0.005, α < 0.05) indicate an influence of spiritual therapy dzikir and worship—on the patient's ability to control violent behavior. Post-intervention, the different tests revealed a significant difference in the ability to control violent behavior between the intervention and control groups (p = 0.005). The provision of spiritual therapy demonstrated an increase in the average score of patients' ability to control violent behavior. This is attributed to the influence of spiritual beliefs on health and behavior in patient care, fostering increased confidence and a sense of closeness to Allah SWT.